Offshoring and Firm Overlap - Hans-Jörg Schmerer; Stella Capuano; Hartmut Egger; Michael Koch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We set up a model of offshoring with heterogeneous producers that captures two empirical regularities on offshoring firms: larger, more productive firms are more likely to make use of the offshoring opportunity; the fraction of firms that engages in offshoring is positive and smaller than one in any size or revenue category. These patterns generate an overlap of offshoring and non-offshoring firms, which is non-monotonic in the costs of offshoring. In an empirical exercise, we employ firm-level data from Germany to estimate key parameters of the model. We show that ignoring the overlap leads to a severe downward bias in the estimated gains from offshoring, which amounts to almost 60 percent in our model.
Keywords: F10; F16; F12; 330